SKRINING FITOKIMIA DAN PENGARUH VARIETAS PELARUT TERHADAP KADAR ISOFLAVON RIMPANG TEMULAWAK - Dilla, Triani Utami; Emelda, Emelda; Fauzi, rizal (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Curcuma Rhizome (Curcuma xanthorriza) is a plant that is usually mixed into herbal concoctions. One of the compounds that play a role is isoflavone. This compound functions as the main antioxidant that prevents radical reactions in lipid oxidation. This research aims to conduct a phytochemical screening of Curcuma Rhizome extract to determine the effect of solvent type on the levels of isoflavone compounds. This research method is true experimental with a post-control design. Data analysis was carried out using statistical tests to see the influence of different solvents on the levels of isoflavone compounds. Based on the results of phytochemical screening, the acetone extract of Curcuma Rhizomes contains flavonoids, steroids, and tannins. However, the results were negative for alkaloid compounds. The hexane extract of Curcuma Rhizomes positively contains alkaloids, flavonoids, steroids, terpenoids, and tannins. negative results for saponin compounds. The isoflavone levels in acetone extract and Curcuma Rhizome extract were 135.32 ppm ±10.73 and 27.72 ppm ±0.86, respectively. Based on the results of the statistical analysis, it shows that there is a significant difference between the isoflavone levels of acetone extract and hexane extract of Curcuma Rhizome (Sig £ 0.05).